2012
DOI: 10.1371/journal.pone.0047051
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Main Mosquito Species in China Based on DNA Barcoding

Abstract: Mosquitoes are insects of the Diptera, Nematocera, and Culicidae families, some species of which are important disease vectors. Identifying mosquito species based on morphological characteristics is difficult, particularly the identification of specimens collected in the field as part of disease surveillance programs. Because of this difficulty, we constructed DNA barcodes of the cytochrome c oxidase subunit 1, the COI gene, for the more common mosquito species in China, including the major disease vectors. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
139
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(157 citation statements)
references
References 31 publications
14
139
0
4
Order By: Relevance
“…Previous studies have proven that COI gene is an efficient and useful barcode for the identification of metazoans, including mosquitoes [21][22][23][24][25][26]. However, COI barcode may not be universally applicable to identify all animal species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have proven that COI gene is an efficient and useful barcode for the identification of metazoans, including mosquitoes [21][22][23][24][25][26]. However, COI barcode may not be universally applicable to identify all animal species.…”
Section: Introductionmentioning
confidence: 99%
“…For example, COI-based barcoding has not been promising in identifying fungi and plant species [27][28][29]. Likewise, COI barcoding has failed to distinguish certain mosquito species of Anopheles and Culex [21][22][23][24][25]. Kumar et al, [23] reported that two closely related mosquito species of the genus Ochlerotatus could not be differentiated using their COI barcode.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] The sequence divergences between species averaged 3.71% (range 2.34-4.50%), which is higher than the threshold of the intra-and interspecific differences (2%). 21 Individuals of a single species always occurred on a common clade, regardless of where they were collected (Figure 1).…”
Section: Resultsmentioning
confidence: 81%
“…Notably, the largest K2P distance (9.13%) observed between specimens from Hokkaido (E-Japan) and Nagasaki (W-Japan) is much greater than the intra-specific K2P divergence (<2%) based on COI barcoding region of mosquitoes (35,36). Maekawa et al (34) also reported a high K2P distance (8.5%) between specimens from Hokkaido (E-Japan) and Wakayama (W-Japan).…”
Section: Accepted Manuscriptmentioning
confidence: 96%